FAKTOR-FAKTOR PENYEBAB ANAK PUTUS SEKOLAH DI KECAMATAN SENAPELAN KOTA PEKANBARU - Ayu Wulandari; M. Razif " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Education is very important for the future of children and the school is the crucible of learning ranging from SD, SMP, SMA and University. In Indonesia has required the 9 (nine) years, but until now there are still many children dropped out of school in the Pekanbaru city Senapelan Subdistrict in this Research. aims to provide an overview of the characteristics of families children dropped out of school and an overview of the factors the causes of children dropping out of school in Senapelan subdistrict. The research method used is qualitative descriptive of a population of 8 children and parents by using the proposive method of sampling techniques which means researchers took based on certain characteristics that are considered to have the relevance of the characteristics corresponding to the research title. The collection of data in research using the method of observation and in-depth interviews to the respondents. Factors that affect the children dropped out of school in this research are economic factors, family, school, and accessibility. Among these factors, factors cause dropouts in Elementary and junior high school levels are economic factors and family.Keywords: factor causes, school age, dropping out of school.